The Relationship between the Level of Dependence and Duration of Gadget Use with Anxiety in Adolescents - Rusni Bano; Rif’atul Fani (Universitas Muhammadiyah Palu, 2026)
The increasing use of gadgets among adolescents may affect mental health, particularly anxiety levels. This study aimed to determine the relationship between gadget dependency levels and anxiety among adolescents at SMA Negeri 1 Wonosari. This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 60 respondents selected using a total sampling technique. The instruments used were the Smartphone Addiction Scale (SAS) and the Generalized Anxiety Disorder-7 (GAD-7). Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most respondents had moderate levels of gadget dependency and anxiety. Statistical analysis revealed a significant relationship between gadget dependency and anxiety levels among adolescents (p < 0.05). Adolescents with higher levels of gadget dependency tended to experience higher anxiety levels. Excessive gadget use may negatively affect emotional balance, sleep quality, and social interaction among adolescents. In conclusion, gadget dependency is associated with anxiety levels among adolescents. Therefore, adolescents are expected to use gadgets wisely to reduce the risk of mental health problems.